2014
DOI: 10.3389/fncir.2014.00093
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine modulation of learning and memory in the prefrontal cortex: insights from studies in primates, rodents, and birds

Abstract: In this review, we provide a brief overview over the current knowledge about the role of dopamine transmission in the prefrontal cortex during learning and memory. We discuss work in humans, monkeys, rats, and birds in order to provide a basis for comparison across species that might help identify crucial features and constraints of the dopaminergic system in executive function. Computational models of dopamine function are introduced to provide a framework for such a comparison. We also provide a brief evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 213 publications
(296 reference statements)
1
110
1
Order By: Relevance
“…[21][22][23] Moreover, dopamine deficit, as a frequently suggested cause of PLMS, 4 also plays a key role in neurodegeneration and affects particularly the prefrontal cortex area, which regulates executive function. 24,25 Previous research suggests that executive function is a better predictor of functional decline and mortality in older women 26 ; thus, the current finding on PLMS and decline in executive function might have important clinical implications. Finally, PLMS could be a marker of sleep fragmentation, 2 and there is increasing recognition on the role of sleep disturbances in cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
“…[21][22][23] Moreover, dopamine deficit, as a frequently suggested cause of PLMS, 4 also plays a key role in neurodegeneration and affects particularly the prefrontal cortex area, which regulates executive function. 24,25 Previous research suggests that executive function is a better predictor of functional decline and mortality in older women 26 ; thus, the current finding on PLMS and decline in executive function might have important clinical implications. Finally, PLMS could be a marker of sleep fragmentation, 2 and there is increasing recognition on the role of sleep disturbances in cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
“…Given that disruption of the excitation/inhibition balance in the PFC has been associated with many aforementioned psychiatric disorders such as schizophrenia (Krause et al, 2013; Lisman, 2012; Winterer and Weinberger, 2004; Yizhar et al, 2011) and ADHD (Moll et al, 2003; Pouget et al, 2009; Won et al, 2011), the individual actions as well as cooperative effects of both transmitters on synaptic transmission, intracellular signaling, and neuronal integration within immature and mature PFC circuitry are thus critical for the execution of prefrontal functions. How NE and DA, individually or synergistically, activate their respective receptors and the effects this on prefrontal functioning at the cellular, physiological, and behavioral level has been well-studied and reviewed in the past (Arnsten, 2011; Arnsten and Pliszka, 2011; Arnsten et al, 2015a; Arnsten et al, 2012b; Berridge and Waterhouse, 2003; Berridge and Arnsten, 2013; Brennan and Arnsten, 2008; Clark and Noudoost, 2014; Puig et al, 2014; Ramos and Arnsten, 2007; Seamans and Yang, 2004; Spencer et al, 2015; Tritsch and Sabatini, 2012). Nevertheless, recent compelling evidence demonstrates that the functional interaction between NE and DA exerts powerful biological effects by activating converging synaptic pathways in PFC circuitry; however this interaction has yet to be well characterized.…”
Section: The Roles Ne and Da Play In Regulating Prefrontal Synaptimentioning
confidence: 99%
“…At the clinical level, various studies have also shown that ADHD patients manifest significant WM impairments (Kofler, Rapport, Bolden, Sarver, & Raiker, ; Martinussen, Hayden, Hogg‐Johnson, & Tannock, ), which may also be partially explained by the significant catecholaminergic role in WM processing (see Puig, Rose, Schmidt, & Freund, for a review). This raises the question of whether the involvement of beta oscillations in WM might also explain the WM impairments in patients with ADHD.…”
Section: Introductionmentioning
confidence: 99%